Transarterial embolization of secondary inferior and superior mesenteric artery arteriovenous fistulas: a systematic review - Abhinandan Ruge; Nidhi Kumar; Lija K. Jose; Vidya Mahalmani (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Acquired arteriovenous fistula are rare complications of a piercing injury, including a gunshot or knife injury, the rupture of a preexisting aneurysm into a neighboring vein, or a complication of arterial catheterization or abdominal surgical techniques, most often colonic resection. Our aim was to develop an online systematic review of the literature to determine all documented incidents of endovascular embolization of secondary mesenteric Arteriovenous Fistula, spanning key databases as well as pertinent publications, from 1982 to 2019. Our case was included as well. The primary objectives were technical success and death; the secondary outcomes were the frequency of complications and the advice of the operators. Main body Forty articles, comprising 41 patients, including our own, were reviewed. The superior mesenteric vessels are the most commonly affected by fistulas. Endovascularembolization was used in 80% of the cases. 100% of the patients had technical success. The intraoperative death rate was 0%, with a 90-day mortality rate of 8%, half of which was unrelated to the original pathology. More than 60% of patients who underwent successful treatments had no severe problems. All others had uneventful recoveries, with only 12% experiencing mild problems that were managed conservatively. Conclusions The majority of authors supported this therapeutic approach thereby making endovascular glue embolization the treatment of choice for superior mesenteric arteriovenous fistula and inferior mesenteric arteriovenous fistula in high risk patients and in patients with multiple co-morbidities.